2014
DOI: 10.18632/oncotarget.1990
|View full text |Cite
|
Sign up to set email alerts
|

Week one FLT-PET response predicts complete remission to R-CHOP and survival in DLBCL

Abstract: Despite improved survival in the Rituximab (R) era, a considerable number of patients with diffuse large B-cell lymphoma (DLBCL) ultimately die from the disease. Functional imaging using [18F]fluorodeoxyglucose-PET is suggested for assessment of residual viable tumor very early during treatment but is compromised by non-specific tracer retention in inflammatory lesions. The PET tracer [18F]fluorodeoxythymidine (FLT) as surrogate marker of tumor proliferation may overcome this limitation. We present results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 42 publications
(32 reference statements)
0
44
0
Order By: Relevance
“…Time between end of cycle and FLT iPET was 9.8 ± 1.9 days for cohort 1 and 9.4 ±1.2 days for cohort 2. Complete proliferative response (CPR) was observed in 29 patients (grade 1, n= 21; grade 2, n= 7; grade 3, n=1), including three patients without baseline FLT PET: since aggressive lymphoma is FL-avid at baseline (1416), lack of uptake in residual nodes on iPET was considered CPR. The other 26 patients showed partial response (grade 4, n= 22) or progression (grade 5, n= 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time between end of cycle and FLT iPET was 9.8 ± 1.9 days for cohort 1 and 9.4 ±1.2 days for cohort 2. Complete proliferative response (CPR) was observed in 29 patients (grade 1, n= 21; grade 2, n= 7; grade 3, n=1), including three patients without baseline FLT PET: since aggressive lymphoma is FL-avid at baseline (1416), lack of uptake in residual nodes on iPET was considered CPR. The other 26 patients showed partial response (grade 4, n= 22) or progression (grade 5, n= 4).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies (14,15) FLT ΔSUV on iPET after one cycle emerged as a predictor of survival, but baseline FLT-SUV did not. An optimal cut-point was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…FLT-PET may also have potential application in evaluating the addition of novel therapies to current re-induction regimens 137 , as well as identifying future non-responders to R-CHOP treatment among aggressive B-cell NHL's by their high FLT uptake and proliferation rate, enabling a risk-adapted treatment approach in these patients 138 . In two recent studies, higher reduction in FLT uptake on interim FLT-PET was a predictor of improved PFS and OS in patients with aggressive lymphomas 139, 140 . A recent pilot study has demonstrated that FLT uptake in bone marrow may be useful for assessment of treatment response as early as 2 days after chemotherapy initiation in AML patients 141 .…”
Section: Future Directionsmentioning
confidence: 95%
“…Baseline FLT uptake has been shown to be a negative predictor of response to rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in DLBCL and was significantly correlated with the International Prognostic Index (18). Moreover, preliminary studies have shown that FLT PET allows noninvasive assessment of tumor grading and early response assessment (19)(20)(21)(22)(23)(24).…”
Section: Nuclear Medicine: Early Therapeutic Monitoring Of Dlbcl: Fltmentioning
confidence: 99%